Halal tourism research bibliometric analysis in Scopus, ProQuest and Ebscohost / Mohd Nasir Ismail ...[et al.] - Ismail, Mohd Nasir; Ismail@Ahmad, Muslim; Othman, Roslina; Ismail, Mohd Saufi (2019)
With the emerging and increasing interest toward halal product and services, a variety of halal based research can be found in online databases. Halal tourism in research is a quite recent topics in journal articles. Halal tourism subtopics has evolved into many subtopics such as halal culinary, halal destination, halal friendly hotel, halal lodging and halal tourism supply chain. With the use of bibliometric analysis and using Scopus analyzer and VOSviewer, this paper attempts to analyse and visualize research output made in the topic of halal tourism. Data are citations from Scopus, ProQuest and Ebscohost databases using 'halal tourism' as keyword. The data corpus are set for research articles in English and the date range set for 1987 to 2019. Total data collection is 383 citations. This paper aims to discover the subject relation of halal tourism research topics in Scopus, ProQuest and Ebscohost. From this research, related topics of halal tourism can be identified and analysed. Authors and journals of halal tourism would also be analysed